PENDIDIKAN AGAMA ISLAM YANG BERMAKNA PADA ANAK USIA DINI - Muzakki, Akhmad (Jurnal Tawadhu, 2020)
Moral education is the soul of Islamic religious education. Achieving perfect morals is the true goal of education. The purpose of moral education is to form people who are virtuous, hard-willed, polite in speaking and acting, noble in behavior and mannerisms, wise, perfect, polite, and civilized, sincere, honest and holy.Moral education is related to tarbiyah, because tarbiyah is instilling the main morals, noble character and noble education especially in the soul of a child, from childhood until he becomes until he becomes a person who has the power to live with his own business and energy abilities. While children are little people who have potential that still needs to be developed.In the perspective of Islam, children have a strategic place on the continuity of human life in the world and continue to build civilization. Childhood is the most important period in education, because when children receive less attention at the beginning of their lives, most of it becomes large with corrupt, lying, jealous, thief, detractor, mocking, and interference in other people's business. Such children will tend to make conspiracies, tricks and plunge others